2018
DOI: 10.1007/s11097-018-9564-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal experience in mania

Abstract: The paper examines both the phenomenology of the manic self as well as critical aspects of manic neurobiology, focusing, with respect to both domains, on manic temporality. We argue that the distortions of lived time in mania exceed mere acceleration and are fundamental for manic affectivity. Mania involves radical acceleration and radical asynchronicity, which result in an instantaneous existence. People with mania rebel against the facticity of reality and suffer from an existential leap towards the future, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The reported changes in the experience of the self by the subject matched Moskalewicz and Schwartzs' (2018) description of the manic self [17]. They showed how manic temporality and the manic self were intertwined.…”
Section: Discussionsupporting
confidence: 77%
“…The reported changes in the experience of the self by the subject matched Moskalewicz and Schwartzs' (2018) description of the manic self [17]. They showed how manic temporality and the manic self were intertwined.…”
Section: Discussionsupporting
confidence: 77%
“…Duration perception research confers unique opportunities to theories of consciousness to test other aspects of experience besides the timing of object awareness. The rate of temporal flow is subjectively reportable and consistencies are found in optimal and suboptimal conditions such as: 1) high flow states during peak experiences (Nakamura & Csikszentmihalyi, 2002, 2014 or mania (Bschor et al, 2004;Mezey & Knight, 1965;Moskalewicz & Schwartz, 2018); and 2) low flow states when bored (Zakay, 2014) or depressed (Thönes & Oberfeld, 2015). Further to this, given that Bayesian PEM is a quantitative and empirically verifiable theory, there is also opportunity to test for differences in Bayesian inference as a corollary of duration perception and conscious experience.…”
Section: Consciousness and Duration Within The Experienced Momentmentioning
confidence: 99%
“…At the opposite extreme, the experience of time is accelerated in situations where cognitive processing is optimal and perceived delays are minimal (i.e., the opposite of boredom) in what is commonly called a 'flow state' (Csikszentmihalyi, 1975). Similarly, people in a manic state of hyperarousal also tend to experience time as accelerated (Bschor et al, 2004;Mezey & Knight, 1965;Moskalewicz & Schwartz, 2018). Many studies and theoretical models have demonstrated that arousal is a key accelerant of time experience (Gil & Droit-Volet, 2012), but attention to time is also a critical factor (Burle & Casini, 2001;Glicksohn, 2001).…”
Section: Introductionmentioning
confidence: 99%